(untitled) (Journal of Oriental Studies, 2023)
The role of information technology in the creation and dissemination of ideas in the public domain has increased significantly, and stateless peoples benefit the most from this. Unlike traditional forms of media (press, radio, television), these information flows are extremely difficult to control by state institutions and power structures, which further increases their effectiveness and applicability. This fact is well understood by the Kurdish diaspora as a user of information technology as a identity-building and nation-building tool.